Investor attention and return reversal in sneakers resale market - Deliana Deliana; Irwan Adi Ekaputra (Jurnal Keuangan dan Perbankan, 2020)
Sneakers, traditionally refer to rubber-soled shoes, are worth more than just footwear nowadays. Resellers believe that sneakers may be considered an investment-grade item due to the profit they booked in recent years. To the best of our knowledge, no former research has investigated the sneakers' resale market behavior specifically. Considering the global sneakers resale market's growth, we aim to analyze investor attention's association with sneakers' return in the sneakers resale market. We use hand-collected sneakers data from StockX.com website and Google Search Volume Index (SVI) as the proxy of investor attention. Based on the system GMM dynamic panel data analysis using some best-seller sneakers as the sample, we conclude that an increase in investor attention tends to increase the sneakers' return as well. Furthermore, the GMM and Fama-Macbeth regression results robustly show short-term return reversals indicated by the negative impact of sneakers' return in the previous period to sneakers' return in the current period. The return reversal may indicate that sneakers' price and return are driven by attention-grabbing information rather than fundamental value.JEL Classification: G11, G14DOI: https://doi.org/10.26905/jkdp.v24i3.4434